Chicagoland Detective Agency. The Maltese mummy 2 - Robbins, Trina (Chicagoland Detective Agency, 2011)
As the founders of the Chicagoland Detective Agency, a haiku-writing girl and a boy with a talking dog have more than enough cases on their hands (and paws) when a friend vanishes, a mummy's amulet disappears, and an evil scientist stalks human brains and hearts.